ТЎСИҚСИЗЛИК КАТЕГОРИЯСИ ВА ТИЛ МАЗМУНИЙ СТРУКТУРАСИ ХУСУСИДА (Scientific journal of the Fergana State University, 2023)
This article deals with linguistic picture of the world, relationship among language codes, particularly, the concessive category and it’s position in the semantic structure.